Peran Masyarakat dalam Pengembangan Produk Pariwisata di Desa Wisata Les, Kecamatan Tejakula, Kabupaten Buleleng (Jurnal Destinasi Pariwisata, 2025)
This study is motivated by the importance of community involvement in the development of community-based tourism, particularly in Les Tourism Village, Tejakula District, Buleleng Regency, which has the potential for nature, cultural, and marine tourism. The aim of this research is to analyze the role of the local community in each stage of tourism product development in the village. A descriptive qualitative method was employed, using data collection techniques such as observation, in-depth interviews, and documentation. The results show that the community of Les Tourism Village is involved in the planning, implementation, management, and evaluation stages of tourism product development. However, their participation tends to fall into the category of induced participation, where involvement is triggered by external encouragement, such as from the village government and tourism awareness groups (Pokdarwis) through socialization and training activities. Although opportunities for participation have started to open up, decision-making processes are still largely influenced by external actors. The main challenges include limited accessibility, inadequate supporting infrastructure, and a lack of human resource skills. This study concludes that enhancing active and independent community participation is essential for achieving sustainable tourism product development. Therefore, strategies that position the community as the main actor in the development process, supported by continuous assistance from relevant stakeholders, are necessary.